Massive endobronchial hemorrhage leading to Cardiac arrest during EBUS-TBNA: a case of successful resuscitation - Ping-Yang Hong; Mao-Hong Huang; Ling Cai; Yi-Yuan Chen; Yu-Xin Guo; Xiao-Bin Zhang (BMC Pulmonary Medicine)
Abstract Introduction : Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is commonly used for diagnosing mediastinal lymphadenopathy. Despite a low complication rate, severe hemorrhage can occur which is reported in this literature, particularly in hypervascular conditions like Castleman disease. Methods A 54-year-old male with idiopathic multicentric Castleman disease underwent EBUS-TBNA for mediastinal lymph node sampling. During the procedure, vascular invasion led to significant bleeding, requiring immediate interventions including suctioning and therapeutic bronchoscopy. Results The patient experienced massive hemorrhage, resulting in airway obstruction, oxygen desaturation, and cardiac arrest. Aggressive resuscitation successfully restored cardiac rhythm after 15 min. The patient was then stabilized and transferred to the intensive care unit for monitoring. Conclusions This case underscores the risk of severe hemorrhage in hypervascular conditions during EBUS-TBNA. Pre-procedural imaging, careful planning, and immediate availability of hemostatic measures are crucial to reducing complications and improving outcomes in high-risk patients.